Total Synthesis of Acetylcholinesterase Inhibitor Macakurzin C - Lee, Dongjoo; Shin, Iljin; Ko, Eunjae; Lee, Kiyoun; Seo, Seung-Yong; Kim, Hyoungsu (Synlett, 2014)
A concise total synthesis of macakurzin C has been accomplished in nine steps (21% overall yield) from commercially available phloroglucinol, featuring a sequential aromatic Claisen rearrangement–cyclization.
Keywords: total synthesis; natural products; aromatic Claisen rearrangement; acetylcholinesterase inhibitors; flavonoids